A Chinese Herbal Formula Ameliorates Pulmonary Fibrosis by Inhibiting Oxidative Stress via Upregulating Nrf2 - Bai, Yunping; Li, Jiansheng; Zhao, Peng; Li, Ya; Li, Meng; Feng, Suxiang; Qin, Yanqin; Tian, Yange; Zhou, Tiqiang (Frontiers in Pharmacology, 2018)
This study aimed to explore the protective effects of a Chinese herbal formula, Jinshui Huanxian formula (JHF), on experimental pulmonary fibrosis and its underlying mechanisms. After being treated with single dose of bleomycin (5 mg/kg) intratracheally, rats were orally administered with JHF and pirfenidone from day 1 to 42, then sacrificed at 7, 14, 28 or 42 days post-bleomycin instillation. JHF ameliorated bleomycin-induced pathological changes, collagen deposition in the rat lung and recovered pulmonary function at different days post-bleomycin instillation. In lungs of JHF-treated rats, the levels of total superoxide dismutase, catalase and glutathione were higher, and myeloperoxidase and methane dicarboxylic aldehyde were lower than those in vehicle-treated rats, respectively. Additionally, JHF inhibited the expression of NADPH oxidase 4 (NOX4) and increased the Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2) in lung tissues. In vitro, JHF and ruscogenin, a compound of Ophiopogonis Radix contained in JHF, significantly inhibited transforming growth factor β1 (TGF-β1)-induced differentiation of fibroblasts. Furthermore, JHF markedly decreased the level of reactive oxygen species in TGF-β1-induced fibroblast. In line with this, upregulation of NAD(P)H: Quinone oxidoreductase 1 and Heme oxygenase 1, and downregulation of NOX4 were found in JHF-treated fibroblast induced by TGF-β1. While on the other hand, Nrf2 siRNA could suppress the JHF-mediated inhibition effect on alpha-smooth muscle actin (α-SMA), and FN1 expression induced by TGF-β1 in fibroblasts. These results indicated that JHF performed remarkably therapeutic and long-term effects on pulmonary fibrosis in rat and suppressed the differentiation of fibroblast into myofibroblast through reducing the oxidative response by upregulating Nrf2 signaling. It might provide a new potential natural drug for the treatment of pulmonary fibrosis.